A review of the Japanese species of the genus Scardia Treitschke (Lepidoptera, Tineidae), with description of a new species - Osada, Yohei; Sakai, Makoto; Hirowatari, Toshiya (Zootaxa, 2016)
Taxonomy of the Japanese species of the genus Scardia is reviewed, and a new species, namely Scardia fusca sp. nov., is described based on the adult morphology.